Produktivitas Pekerja Wanita Perajin Tenun Ikat di Kabupaten Klungkung - Padma Dewi, I Gusti Ayu; Setyadhi Mustika, Made Dwi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 10, Oktober 2015 (pp.1194-1327), 2015)
Female labor force participation is the first step to achieve real equality between women and men. This study aimed to analyze the productivity of female workers artisans weaving in Klungkung regency. The data used in this research is primary data. The data analysis technique that used in this research is Moderated Regression Analysis. The analysis showed the variables of education, age, husband’s income and number of dependent children simultaneously affect the labor productivity of women artisans weaving in Klungkung regency. Partially education and number of dependent children does not affect the productivity of female workers, whereas the husband's income and age affect the productivity of female workers. The analysis also showed that skills as a moderating variable of education on worker productivity and moderating age of woman worker productivity. Skills are variables that can increase the productivity of female workers.
Keywords: education, age, husband' s income, number of dependent children, the skills and productivity of women workers